pH homeostasis links the nutrient sensing PKA/TORC1/Sch9 ménage-à-trois to stress tolerance and longevity - Deprez, Marie-Anne (2018)
The plasma membrane H+-ATPase Pma1 and the vacuolar V-ATPase act in close harmony to tightly control pH homeostasis, which is essential for a vast number of physiological processes. As these main two regulators of pH are responsive to the nutritional status of the cell, it seems evident that pH homeostasis acts in conjunction with nutrient-induced signalling pathways. Indeed, both PKA and the TORC1-Sch9 axis influence the proton pumping activity of the V-ATPase and possibly also of Pma1. In addition, it recently became clear that the proton acts as a second messenger to signal glucose availability via the V-ATPase to PKA and TORC1-Sch9. Given the prominent role of nutrient signalling in longevity, it is not surprising that pH homeostasis has been linked to ageing and longevity as well. A first indication is provided by acetic acid, whose uptake by the cell induces toxicity and affects longevity. Secondly, vacuolar acidity has been linked to autophagic processes, including mitophagy. In agreement with this, a decline in vacuolar acidity was shown to induce mitochondrial dysfunction and shorten lifespan. In addition, the asymmetric inheritance of Pma1 has been associated with replicative ageing and this again links to repercussions on vacuolar pH. Taken together, accumulating evidence indicates that pH homeostasis plays a prominent role in the determination of ageing and longevity, thereby providing new perspectives and avenues to explore the underlying molecular mechanisms.